“Beige” Cross Talk Between the Immune System and Metabolism - Banfai, Krisztina; Ernszt, David; Pap, Attila; Bai, Peter; Garai, Kitti; Belharazem, Djeda; Pongracz, Judit E.; Kvell, Krisztian (Frontiers in Endocrinology, 2019)
With thymic senescence the epithelial network shrinks to be replaced by adipose tissue. Transcription factor TBX-1 controls thymus organogenesis, however, the same TBX-1 has also been reported to orchestrate beige adipose tissue development. Given these different roles of TBX-1, we have assessed if thymic TBX-1 expression persists and demonstrates this dualism during adulthood. We have also checked whether thymic adipose involution could yield beige adipose tissue. We have used adult mouse and human thymus tissue from various ages to evaluate the kinetics of TBX-1 expression, as well as mouse (TEP1) and human (1889c) thymic epithelial cells (TECs) for our studies. Electron micrographs show multi-locular lipid deposits typical of beige adipose cells. Histology staining shows the accumulation of neutral lipid deposits. qPCR measurements show persistent and/or elevating levels of beige-specific and beige-indicative markers (TBX-1, EAR-2, UCP-1, PPAR-gamma). We have performed miRNome profiling using qPCR-based QuantStudio platform and amplification-free NanoString platform. We have observed characteristic alterations, including increased miR21 level (promoting adipose tissue development) and decreased miR34a level (bias towards beige adipose tissue differentiation). Finally, using the Seahorse metabolic platform we have recorded a metabolic profile (OCR/ECAR ratio) indicative of beige adipose tissue. In summary, our results support that thymic adipose tissue emerging with senescence is bona fide beige adipose tissue. Our data show how the borders blur between a key immune tissue (the thymus) and a key metabolic tissue (beige adipose tissue) with senescence. Our work contributes to the understanding of cross talk between the immune system and metabolism.